An indigenous psychology perspective for appropriate mental health services and research in Indonesia - Ranimpi, Yulius Yusak; Hyde, Merv; Oprescu, Florin (Buletin Psikologi, 2023)
Even though culture has been recognized and discussed by many scholars over decades in mainstream psychology, this aspect was treated only in terms of superficial manifestations and as a picture that represents different stages of social evolution or development. Indigenous psychology is an effort to rehash and refresh the importance of cultural aspects and their diversities in psychology and emplaces it as a vital way to understanding people from their perspective, in the real world. This approach believed that human being can construct their world. Knowledge and reality are psychological and social phenomena that are constructed by a human being. In terms of knowledge, indigenous psychology wants to claim that the truth is contextual-owned, experienced, believed, and lived by a human being. Especially in mental health and poverty issues and its interconnection in Indonesia must be treated as a psychological and social phenomenon that is socially constructed by people in their setting